Administración financiera del capital de trabajo en la empresa Fuerte Care SAS de la ciudad de Palmira Valle del Cauca (2023)
The financial administration of working capital has been consolidated as an essential pillar in the evolution and sustainability of micro, small and mediumsized enterprises (MSMEs). Through efficient management of current resources, these companies can optimize their liquidity, maximize their profitability and reduce financial risks. (Silva et al., 2018).